Observation of High Doppler Velocity Wings in the Nascent Wind of R Doradus - Do, Hoai Thi; Pham, Nhung Tuyet; Pham, Tuan-Anh; Darriulat, Pierre; Pham, Diep Ngoc; Nguyen, Phuong Thi; Tran, Thai Thi (Communications in Physics, 2020)
We study the morpho-kinematics in the nascent wind of AGB star R Doradus in the light of high Doppler velocity wings observed in the spectral lines of several species. We probe distances from the star between ∼10 and ∼100 au using ALMA observations of the emission of five different molecular lines. High Doppler velocity enhancements of the line emission are observed in the vicinity of the line of sight crossing the star, reminiscent of those recently interpreted as gas streams in the nascent wind of a similar AGB star, EP Aqr. They are present in both blue-shifted and red- shifted hemispheres but are not exactly back-to-back. They are accelerated at a typical rate of 0.7 km s\(^−1\) au\(^−1\) up to some 20 km s\(^−1\). Important differences are observed between the emissions of different molecules. We exclude an effect of improper continuum subtraction. However, in contrast to EP Aqr, the line of sight plays no particular role in the R Dor morpho-kinematics, shedding doubt on the validity of a gas stream interpretation. We discuss possible interpretations in terms of stellar pulsations or of rotation of the gas in the environment of the star. We conclude that, in the state of current knowledge, no fully convincing picture of the physics governing the production of such high velocities, typically twice as large as the terminal velocity, can be reliably drawn. New high resolution analyses of observations of the nascent wind of oxygen-rich AGB stars are needed to clarify the issue.